OBESITY CHILD: CAUSES, CONSEQUENCES AND PHYSICAL ACTIVITY (Fiep Bulletin - online, 2017)
In Brazil, obesity still a sad reality, though malnutrition. The Child obesity has nearly doubled in the last 10years and it is estimated that about 15% of Brazilian children are obese. Given the above, the present study aims to provide answersabout the causes and consequences taking into account the theoretical references on the subject and discriminating againstchildhood obesity rate in school, investigating the possible causes that led to obesity. In this sense, we intend to demonstrate in frontof their diseases and sequelae presented by obese children, and bringing the academies a new segment of society, since it is notclear, children and adolescents being treated in physical activities in order to assist them in reduction of diseases caused by obesity.